(untitled) (Journal on studies and research of academic knowledge, 2022)
The objective of the study was to promote the participation of rural women in a neighborhood through empowerment strategies, to improve their living conditions, for this purpose, 30 rural women were selected from the Santa Ana Committee of the District of Capitán Miranda, department of Itapúa, the study methodology was developed with a qualitative approach, in a framework of Research - Action - Participatory (RAP) in the years 2020 to 2021. It began with the first meetings between internal and external agents, to familiarize them with their context, achieving awareness and collaboration of rural women, who, already empowered, contributed to the construction of a diagnosis of the socioeconomic context and the identification of their needs and interests to start with the production planning. It is concluded that 60% of them have achieved a critical awakening of their reality, developing their capacity for self-management, empowerment, willpower to move forward and improve their living conditions, after applying the knowledge acquired in the training and workshops.